2020
DOI: 10.1177/0145561320980186
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Follow-Ups for Vertigo/Dizziness Outpatients

Abstract: Objectives: In the present report, we aimed to investigate the impact of the coronavirus disease (COVID-19) pandemic on vertigo/dizziness outpatient cancellations in Japan. Methods: We examined 265 vertigo/dizziness outpatients at the ear, nose, and throat department of the Nara Medical University between March 01, 2020, and May 31, 2020, during the COVID-19 pandemic in Japan. We also focused on 478 vertigo/dizziness outpatients between March 01, 2019, and May 31, 2019, before the COVID-19 pandemic, to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…However, the incidence at our institution during the pandemic year period was higher in comparison to the previous two years. This was due to a reduction in the overall number of outpatient visits, as previously reported [3] , [10] . This is consistent with the pandemic restrictions enforced by the Italian government that limited activity to urgent and oncological cases, so patients with acute audiological symptoms were admitted to the clinic while patients with slowly progressive hearing loss, or other mild audiological symptoms were postponed (see Table 1 ).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…However, the incidence at our institution during the pandemic year period was higher in comparison to the previous two years. This was due to a reduction in the overall number of outpatient visits, as previously reported [3] , [10] . This is consistent with the pandemic restrictions enforced by the Italian government that limited activity to urgent and oncological cases, so patients with acute audiological symptoms were admitted to the clinic while patients with slowly progressive hearing loss, or other mild audiological symptoms were postponed (see Table 1 ).…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, the total outpatient audiological visits performed at our institution during 2020 showed a notable reduction [10] . Ueda et al [3] investigated the impact of the COVID-19 pandemic on vertigo/dizziness outpatient cancellations. They found a 45% reduction in the total number of vertigo-associated visits between March and May 2020 in comparison to the same period of 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding DMP consultations, one in six CAD patients in our study reported not going to regular DMP consultations any longer since the outbreak of the COVID-19 pandemic, whereas only a minor group of patients who already had a scheduled appointment decided to cancel or postpone it. Specifically, the fear of infection with COVID-19 accounted for one third of postponed or canceled appointments, which has also been observed in other medical sectors ( 48 , 49 ). This patient group may have tried to cope with the perceived risk due to pre-existing health conditions by a general avoidance behavior toward situations with potentially elevated infection risk—such as doctor's offices –, which has also been reported in other studies ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 69%